2017
DOI: 10.1016/j.compositesb.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the influence of moisture on fatigue damage mechanisms in a woven glass-fibre-reinforced PA66 composite using acoustic emission and infrared thermography

Abstract: A woven glass-fibre-reinforced composite with a polyamide 6,6 matrix is considered for the purpose of being integrated into an automotive part. Fatigue tests were conducted on both [(0/90) 3 ] and [(±45) 3 ] stacking sequences. In order to analyze the influence of moisture content on the fatigue behaviour, samples were conditioned at RH0, RH50 and RH100. Although moisture content affects the fatigue life for high stress levels, this effect tends to disappear for low stress levels. This phenomenon was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Two in-situ non-destructive techniques are used in order to detail the fatigue damage scenario: namely, acoustic emission (AE) and infrared (IR) thermography. These techniques have become recognized non-destructive techniques, commonly used to detect, locate and discriminate defects in traditional composite materials [29][30][31][32][33] as well as PFCs [5,34,35]. AE are transient elastic waves produced by the sudden internal stress redistribution of the materials caused by the changes within the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Two in-situ non-destructive techniques are used in order to detail the fatigue damage scenario: namely, acoustic emission (AE) and infrared (IR) thermography. These techniques have become recognized non-destructive techniques, commonly used to detect, locate and discriminate defects in traditional composite materials [29][30][31][32][33] as well as PFCs [5,34,35]. AE are transient elastic waves produced by the sudden internal stress redistribution of the materials caused by the changes within the structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of studies, a main assumption is done: signals are affected by propagation but they remain images of sources. Therefore, acoustic emission events can be classified using multivariable statistical analysis techniques and then attributed to a damage mechanism in the material [5][6][7][8][9][10][11][12]. The main assumption is: the acoustic signatures are unchanged during propagation and damage evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For the unsupervised pattern recognition, the descriptors should be relevant and limited in number. The possibility to identify AE signatures of damage mechanisms is an established field [5][6][7][8][9][10][11][12]. In most studies, the attribution of system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the WF/HDPE damage and fracture behavior are closely related to the fiber/matrix interface [4]. The damage and failure modes of fiber reinforced polymer composites are mainly divided into fiber pull-out, fiber breakage and delamination, matrix cracking, and fiber-matrix debonding [5,6,7,8,9]. However, it has been difficult to accurately and effectively distinguish the failure modes and understand the evolution of the damage mechanism of high-filled WF/HDPE by using the traditional evaluation methods and testing techniques.…”
Section: Introductionmentioning
confidence: 99%